Role of Serum Procalcitonin in Prediction of Severity in Patients with Acute Cholangitis - Bilal, Mir; Shaheena, Parveen; Chauhan, Ashish; Syed, Mushfiq; Tahir, Majeed; Mir, Nadeem; Najar, Rameez; Acharya, Kalpana (Journal of Gastrointestinal Infections, 2023)
Background Cholangitis is one of the commonest emergencies encountered by gastroenterologists that may warrant drainage of biliary system. Serum procalcitonin (PCT) is an important biomarker of cholangitis with a potential to guide early therapeutic decision.Materials and Methods We did a retrospective analysis of prospectively maintained data of patients admitted in the hospital from March 2018 to September 2020 with a diagnosis of acute cholangitis based on Tokyo 18 guidelines (TG-18). All the demographic parameters, biochemical and hematological parameters, and the result were recorded.Results One-hundred two patients were admitted to our hospital with a mean age of 51.07 ± 7.99 years, among which 58.5% (59/102) were females with most common etiology being choledocholithiasis (64%). Fever, jaundice, and abdominal pain were seen in 78% (80/102), 73.3% (74/102), and 76.9% (78/102) of patients, respectively. Organ failure was seen in 29.3% (29/102) of patients with most common organ failure being acute kidney injury. Mild, moderate, and severe cholangitis as per TG-13 was seen in 43.9, 26.8, and 29.3% of patients, respectively. Elevated PCT levels were associated with severe disease (76.7 vs. 26.5%, p < 0.05). Forty-three percent (44/102) patients were managed with delayed biliary drainage, while the majority of remaining specifically with raised PCT levels needed early endoscopic intervention.Conclusion In this retrospective analysis, we showed that most common etiology of cholangitis in was choledocholithiasis. Raised serum PCT levels were significantly associated with increased severity of cholangitis.
Keywords: cholangitis; choledocholithiasis; procalcitonin